2023
DOI: 10.1017/psrm.2023.33
|View full text |Cite
|
Sign up to set email alerts
|

Affective polarization and coalition signals

Markus Wagner,
Katrin Praprotnik

Abstract: Affective polarization between partisans is potentially troubling for liberal democracy. Hence, recent research has focused on how affective dislike between partisans can be reduced. Using a survey experiment in Austria, we test whether elite signals matter. Respondents exposed to fictional news stories implying that their in-party might form a coalition with an out-party show reduced dislike toward supporters of that out-party. Our experiment also shows that coalition signals can influence out-party affect ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…They demonstrate experimentally that information signals that a unity government between left and right will be formed leads to warmer evaluations across the left‐right partisan divide. Using a similar research design, Praprotnik and Wagner (2021) report similar results from an experiment conducted in Austria. Beyond these country‐specific studies, a broad comparative experimental study conducted in 25 European polities similarly concluded that ‘coalition partnership significantly lessens affective polarization’ (Hahm et al., 2023, p. 2).…”
Section: Theoretical Expectationsmentioning
confidence: 67%
See 2 more Smart Citations
“…They demonstrate experimentally that information signals that a unity government between left and right will be formed leads to warmer evaluations across the left‐right partisan divide. Using a similar research design, Praprotnik and Wagner (2021) report similar results from an experiment conducted in Austria. Beyond these country‐specific studies, a broad comparative experimental study conducted in 25 European polities similarly concluded that ‘coalition partnership significantly lessens affective polarization’ (Hahm et al., 2023, p. 2).…”
Section: Theoretical Expectationsmentioning
confidence: 67%
“…Based on work in political psychology, and specifically social identity theory, we expect that those who perceive themselves as winners of the elections will express lower levels of partisan dislike towards out‐parties (Sheffer, 2020). Second, in line with work on coalition heuristics, we hypothesize that shared governance is reflected in warmer affective evaluations among supporters of co‐governing parties (Horne et al., 2023; Praprotnik & Wagner, 2021). These two mechanisms serve as affective pressure valves, leading to post‐election decline in out‐party negative affect.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation